Effects of dietary whole grain buckwheat and oat on benzo[a]pyrene-induced genotoxicity, oxidative and pyroptotic injury in liver of mice. (June 2022) - Li, Hao; Yuan, Li; Wang, Zhulin; Shi, Lin; Dong, Rui; Hu, Xinzhong
Graphical abstract: Highlights: Whole grain diet reduced the genotoxicity induced by benzo[a]pyrene in mice. Whole grain diet reversed the oxidative damage of liver in mice induced by benzo[a]pyrene. Whole grain diet could inhibit benzo[a]pyrene-induced pyroptotic injury in liver of mice to a certain extent. Abstract: Benzo[a]pyrene (BaP), as a highly toxic substance, exists in the surrounding and foods of people's life and poses a great threat to the human body. Our previous studies have shown that BaP caused oxidative and pyroptotic damage to the liver, which is an urgent problem to be solved. Whole grains not only contain a series of important nutrients, but also have important significance for preventing obesity, dyslipidemia and inflammation. Therefore, this work tried to use whole grain diet as a new method to inhibit the BaP-induced toxicity in mice. Compared with BaP group, the addition of whole grain buckwheat (WGB) or oat (WGO) diet could improve the appetite of mice, stabilize the levels of ALT, AST, TC and TG in serum, maintain the balance of H2 O2, MDA, GSH-Px and SOD levels in liver tissues, reduce BPDE-DNA adduct content and the mRNA expression of BaP metabolites related enzyme (including CYP1A1, CYP1B1, GST-P1 and AhR). Furthermore, both WGB and WGO could inhibit the pyroptotic markers (NLRP3, Caspase-1, GSDMD) increase and inflammatory factors release, promote the synthesis of Short-chain fatty acids (SCFAs), and the effect of WGO was more excellent than WGB. This study fully verified that the reverse effect of the dietary whole grain on BaP-induced genotoxicity, oxidative and pyroptotic injury in liver of mice, and provided a powerful theoretical support for new toxicity control dietary methods in the future.